Использование разговорных идиом в трагедиях Софокла - Барзах, З. А. (Hyperboreus, 2015)
The purpose of this article is to study different dramatic functions of colloquialisms in Sophoclean tragedy. Apart from the obvious functions of marking low social status of character or oratio agitata, colloquial speech is often used by Sophocles for the sake of its notorious tendency towards ambiguity, understatement, irony or hyperbole. All these features of colloquial speech can serve various purposes in different dramatic contexts. The most striking examples are signiﬁcant ambiguity of colloquial τις for ﬁrst or second person in Ant. 751–752 and the colloquial metaphor in ОТ 1371–1374, the literal meaning of which ﬁts its immediate context all too well.